Diverse Effects of Phytoestrogens on the Reproductive Performance: Cow as a Model - Izabela Wocławek-Potocka; Chiara Mannelli; Dorota Boruszewska; Ilona Kowalczyk-Zieba; Tomasz Waśniewski; Dariusz J. Skarżyński (International Journal of Endocrinology)
Phytoestrogens, polyphenolic compounds derived from plants, are more and more common constituents of human and animal diets. In most of the cases, these chemicals are much less potent than endogenous estrogens but exert their biological effects via similar mechanisms of action. The most common source of phytoestrogen exposure to humans as well as ruminants is soybean-derived foods that are rich in the isoflavones genistein and daidzein being metabolized in the digestive tract to even more potent metabolites—para-ethyl-phenol and equol. Phytoestrogens have recently come into considerable interest due to the increasing information on their adverse effects in human and animal reproduction, increasing the number of people substituting animal proteins with plant-derived proteins. Finally, the soybean becomes the main source of protein in animal fodder because of an absolute prohibition of bone meal use for animal feeding in 1995 in Europe. The review describes how exposure of soybean-derived phytoestrogens can have adverse effects on reproductive performance in female adults.